A REVIEW OF THE DEPARTMENT OF ENGLISH LANGUAGE EDUCATION CURRICULUM DEVELOPMENT - Habib Habiburrahim (Universitas Islam Negeri Banda Aceh, 2018)
A review of the current literature on curriculum development elucidates that much of the existing work either: (i) focuses on the development of educational resources; (ii) rectifies the concept of curriculum; (iii) or identifies desirable features of development methods without providing any practical guidance that synchronizes the needs of any particular education systems and geographical status where students are living. This paper scrutinizes the development of the Department of English Language Education curriculum of Ar-Raniry State Islamic University (Universitas Islam Negeri Ar-Raniry Banda Aceh) Indonesia in line with Aceh context. It is flexible and evolutionary, and is soundly underpinned by proven theory and practices from contemporary curriculum development concepts. Systematically this article explores three pivotal aspects: educational foundation in Aceh, curriculum development in Indonesia, and an ideal curriculum of the Department of English Language Education, particularly in Aceh context.